First record of Haemaphysalis juxtakochi Cooley, 1946 (Acari: Ixodidae) from Peru. - Guglielmone, Alberto Alejandro (2005)
Twenty-four adult ticks were collected from South American alpacas, Lama pacos (Linnaeus, 1758), at Anexo Tambo Cañahuas (16º01?S, 71º26?W), distrito de Yanahuara, departamento Arequipa, Peru, altitude 4,300 m. Three male and 20 female ticks were identified as Amblyomma parvitarsum Neumann, 1901, a common parasite of camelids belonging to the genera Lama G. Cuvier, 1800, and Vicugna Lesson, 1842, in the Andean region of Argentina, Bolivia, Chile and Peru. The remaining tick was a female of Haemaphysalis juxtakochi Cooley, 1946. This is the first Peruvian record of H. juxtakochi, a species known from the Neotropical and southern Nearctic Zoogeographic Regions. Lama pacos is also a new host for this tick species.Lama pacos (Linnaeus, 1758), at Anexo Tambo Cañahuas (16º01?S, 71º26?W), distrito de Yanahuara, departamento Arequipa, Peru, altitude 4,300 m. Three male and 20 female ticks were identified as Amblyomma parvitarsum Neumann, 1901, a common parasite of camelids belonging to the genera Lama G. Cuvier, 1800, and Vicugna Lesson, 1842, in the Andean region of Argentina, Bolivia, Chile and Peru. The remaining tick was a female of Haemaphysalis juxtakochi Cooley, 1946. This is the first Peruvian record of H. juxtakochi, a species known from the Neotropical and southern Nearctic Zoogeographic Regions. Lama pacos is also a new host for this tick species.Amblyomma parvitarsum Neumann, 1901, a common parasite of camelids belonging to the genera Lama G. Cuvier, 1800, and Vicugna Lesson, 1842, in the Andean region of Argentina, Bolivia, Chile and Peru. The remaining tick was a female of Haemaphysalis juxtakochi Cooley, 1946. This is the first Peruvian record of H. juxtakochi, a species known from the Neotropical and southern Nearctic Zoogeographic Regions. Lama pacos is also a new host for this tick species.Lama G. Cuvier, 1800, and Vicugna Lesson, 1842, in the Andean region of Argentina, Bolivia, Chile and Peru. The remaining tick was a female of Haemaphysalis juxtakochi Cooley, 1946. This is the first Peruvian record of H. juxtakochi, a species known from the Neotropical and southern Nearctic Zoogeographic Regions. Lama pacos is also a new host for this tick species.Haemaphysalis juxtakochi Cooley, 1946. This is the first Peruvian record of H. juxtakochi, a species known from the Neotropical and southern Nearctic Zoogeographic Regions. Lama pacos is also a new host for this tick species.H. juxtakochi, a species known from the Neotropical and southern Nearctic Zoogeographic Regions. Lama pacos is also a new host for this tick species.Lama pacos is also a new host for this tick species.